Application of Multifunctional Mechanical Metamaterials. Issue 7 (9th April 2019) - Shanian, Ali; Jette, Francois‐Xavier; Salehii, Mahtab; Pham, Minh Quan; Schaenzer, Megan; Bourgeois, Genevieve; Bertoldi, Katia; Gross, Andrew; Javid, Farhad; Backman, David; Yandt, Scott; Gerendas, Miklos; et al.
Abstract : Mechanical metamaterials have attracted great interest due their ability to attain material properties outside the bounds of those found in natural materials. Many promising mechanical metamaterials have been designed, fabricated, and tested, however, these metamaterials have not been subjected to the rigorous requirements needed to certify their use in demanding industrial applications that require multifunctional behavior. This paper details an auxetic multifunctional metamaterial that has been optimized to outperform conventional designs for cooling systems commonly used in the space, the transportation, the energy and the nuclear industry. Experimental tests performed to certify this material for use in gas turbines have shown that in comparison to conventional designs, the metamaterial increases structural life by orders of magnitude while also providing more efficient cooling and maintaining similar acoustic damping characteristics. This metamaterial offers an agile and economical solution for the realization of next generation components. Abstract : This paper describes the application of auxetic materials for use in high temperature combustion applications. The results of our findings show that our optimized auxetic multifunctional metamaterial outperforms conventional designs for cooling systems commonly used in high temperature industrial applications.